Using solar distillation to treat salty water sub-surface in the Hassi Miloud area (Algeria) for agricultural watering a drop with a drop - Dris Slimani; Abdelkader Souigat; Zineb Korichi; Yamina Benkrima; Fouzi Benbrahim; Yamina Benbessisse; Brahim Labed (Desalination and Water Treatment)
The Hassi Miloud region in Algeria is characterized by an abundance of sub-surface water, but it is not suitable for irrigation due to its extreme salinity. This study presents a method for treating this water in two stages to enhance its suitability for drip irrigation. Firstly, solar distillation was employed to purify the water. Subsequently, the resulting pure water was used to dilute saline water. Our study included treating salt water according to different dilution coefficients corresponding to conductivity 3.0, 2.5, 2.0, 1, 5, 1.0, 0.5, 0.1 mS/cm. Our results showed that the treated water falls within the range of suitability for irrigation for the 0.5 mS/cm sample with a treated water productivity of 3.529 liters/m2 per day, and it is in the excellent range for the 0.1mS/cm sample with a treated water productivity of 3.505 liters/m2 per day.